In vitro feeding of instars of ixodid tick Amblyomma variegatum on skin membranes and its application to the transmission of Theileria mutans and Cowdria ruminantum - Voigt, Wolf P.; Young, A.S.; Mwaura, S.N.; Nyaga, S.G.; Njihia, G.M.; Mwakima, F.N.; Morzaria, S.P. (Cambridge University Press, 1993)
An in vitro feeding method using rabbit or cattle skin membranes, applied successfully to all stages (larvae, nymphae and adults) of the ixodid tick, Amblyomma variegatum, is described. The feeding apparatus consisted of a blood container with a membrane placed on top of a tick containment unit. A carbon dioxide atmosphere of between 5 and 10% and a temperature of 37 °C were used as stimulants for the attachment of the ticks. High CO2 concentrations in the atmosphere improved the feeding success of all instars. The effect of anticoagulation methods for the bloodmeal was investigated, and heparinized blood was found to be the most suitable for tick feeding. When the bloodmeal was replaced by tissue culture medium for feeding nymphs the subsequent moulting success was reduced. Adult ticks of both sexes remained attached for up to 16 days, until completion of their bloodmeals. All stages of the tick fed on whole blood in the artificial feeding system and all reached engorged weights less than those achieved by control ticks fed on experimental animals. A large proportion of ticks, fed artificially on whole blood, moulted or laid eggs successfully. The method was successfully applied for the transmission of Theileria mutans and Cowdria ruminantium to cattle.